Anne J. Cruz, Discourses of poverty: Social reform and the picaresque in early modern Spain. University of Toronto Press, Toronto, 1999; 297 pp. - Manuel Pérez (Nueva Revista de Filología Hispánica, 2003)
Se reseñó el libro: Discourses of poverty: Social reform and the picaresque in early modern Spain.